IDENTIFIKASI AFEKSI PATERNAL PADA AYAH DARI ANAK USIA DINI DI KOTA KUPANG - Beatriks Novianti Kiling, Indra Yohanes, Fitriany Karunia Muh. Wangge, Friandry Windisany Thoomaszen (JIV-Jurnal Ilmiah Visi, 2016)
The father parenting an early aged child with emotion or good paternal affection has various positive effects. However, presumably the fathers in Eastern Indonesia has not implemented it well. This research aims at discovering paternal affection and its relations with demographic factors. Samples used in this research totaled 158 fathers each of which had a child of 0 – 8 years old. The samples were determined by employing incidental sampling technique. The research conducted as from November 2015 through March 2016 used questioner with 10 statement items. The collected data was analyzed with descriptive statistics. The findings showed that the fathers in Kupang City had high paternal affection supporting by the fact that 158 samples of paternal affection were categorized high. The finding proves, the fathers in Kupang City fully realize their important involvement in emotional parenting. The research also discovered several patterns of paternal affection based on the some demographic factors. The positive research findings should be followed up by concerned parties in Kupang City. They also should verify the findings and motivate as well as improve the fathers’ capacity in emotional parenting. This action will assist to clarify the process and the meaning behind the interaction between father’s parenting and early aged child.